Synthesis of oxygen heterocycles - Bedford, Simon Bernard (1993)
In chapter one, the various methods of generating benzenoid orthoquinodimethanes are discussed and approaches to their heterocyclic analogues are also reviewed. The utility of ortho-quinodimethanes in organic synthesis is highlighted by examples of both inter- and intramolecular Diels-Alder cycloadditions as the key steps in the total synthesis of naturally occurring polycyclic systems.